Prototype GaAs X‐ray detector and preamplifier electronics for a deep seabed mineral XRF spectrometer. (2nd November 2017) - Lioliou, G.; Barnett, A.M.
Abstract : Work towards developing a prototype GaAs based X‐ray fluorescence spectrometer focusing on the detector‐preamplifier system for in situ characterisation of deep seabed minerals is presented. Such an instrument could be useful for marine geology and provide insight into hydrothermal processes. It would also be beneficial for deep sea mining applications. The GaAs photodiode was electrically characterised at 4 °C (ambient seawater temperature) and 33 °C. A system energy resolution (full width at half maximum) at 5.9 keV of 580 eV at 4°C, limited by the dielectric noise, broadening to 680 eV at 33°C, was recorded. The spectral performance of the system was characterised across the energy range 4.95 keV to 21.17 keV, at 33°C, using high‐purity X‐ray fluorescence calibration samples excited by a Mo target X‐ray tube. The charge output from the system was found to be linear with incident photon energy. The energy resolution was found to broaden from 695 eV at 4.95 keV to 735 eV at 21.17 keV, attributed to the increasing Fano noise with energy. The same X‐ray tube was used to fluoresce an unprepared manganese nodule (revealing the presence of Mn, Fe, Ni, Cu, Zn, Pb, Sr, and Mo) and a black smoker hydrothermal vent sample (containing Fe, Co, Ni, Cu, Zn, Pb, and Mo). Such a spectrometer may also find use in future space missions to study the hydrothermal vents that are believed to exist in the oceans of Jupiter's moon Europa.